ウミタカマル ニヨル ナンタイヨウ ノ タイキチュウ リュウカジメチル ノウド ソクテイ - 和田, 誠; ワダ, マコト; 中岡, 慎一郎; ナカオカ, シンイチロウ; 笠松, 伸江; カサマツ, ノブエ; Wada, Makoto; Nakaoka, Shin-ichiro; Kasamatsu, Nobue (2011)
P(論文) 2009年1月から2月の南半球の夏期間に,東京海洋大学の研究練習船「海鷹丸」にプロトン移動反応質量分析計を搭載して,南大洋の大気中の硫化ジメチル濃度の連続観測を実施した.海鷹丸は昭和基地沖とケープダンレー沖の氷縁域を含む南大洋を航行し,研究観測を実施した.この海域での大気中の硫化ジメチル濃度の連続観測は初めてである.海水中の硫化ジメチル濃度の観測も行われ,そのデータとの対比が可能となった.大気中の連続観測から,昭和基地沖およびケープダンレー沖の氷縁域では,2ppbを越える高い濃度の硫化ジメチルが観測された. Observations of atmospheric dimethyl sulfide were performed in the Southern Ocean during a cruise from Cape Town to Fremantle on the research vessel Umitakamaru" of the Tokyo University of Marine Science and Technology during the austral summer from January to February 2009. The main observation area was south of 60°S in the Southern Ocean, which includes the margin of Antarctic sea ice. The results represent the first continuous measurements of atmospheric dimethyl sulfide in the area. We also undertook point measurements of dimethyl sulfide in the ocean. High concentrations of dimethyl sulfide (>2ppb) were recorded in the atmosphere at the margin of sea ice off Syowa and off Cape Darnley. departmental bulletin paper